The first principle calculation of green-kubo formula with the two-time ensemble technique - Tian, Chu-Shun (2012)
For weak-coupling electronic plasmas in the presence of small fluctuations, we calculate Green-Kubo formula for transport coefficients employing the ab initio theory, i.e., the two-time ensemble technique. The microscopic interpretations of Onsager's hypothesis on fluctuations are presented in the framework.